2007
DOI: 10.1534/genetics.107.074815
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex Heterozygosity Reduces Fitness in Experimentally Infected Mice

Abstract: It is often suggested that heterozygosity at major histocompatibility complex (MHC) loci confers enhanced resistance to infectious diseases (heterozygote advantage, HA, hypothesis), and overdominant selection should contribute to the evolution of these highly polymorphic genes. The evidence for the HA hypothesis is mixed and mainly from laboratory studies on inbred congenic mice, leaving the importance of MHC heterozygosity for natural populations unclear. We tested the HA hypothesis by infecting mice, produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 50 publications
5
79
1
Order By: Relevance
“…MHC heterozygosity has been shown to be associated with decreased infection rates in both laboratory and field studies (McClelland et al 2003;Froeschke and Sommer 2005), but several other studies have found no such association (Harf and Sommer 2005;Dionne et al 2009). Ilmonen et al (2007) found that wild-derived mice that were MHC heterozygotes did not show better resistance to Salmonella or better survival in semi-natural enclosures, even though earlier laboratory experiments documented a heterozygote advantage (Penn et al 2002). These results emphasise the importance of studies on wild, outbred species.…”
Section: Effects Of the Mhc On Infection And Survival Ratesmentioning
confidence: 75%
“…MHC heterozygosity has been shown to be associated with decreased infection rates in both laboratory and field studies (McClelland et al 2003;Froeschke and Sommer 2005), but several other studies have found no such association (Harf and Sommer 2005;Dionne et al 2009). Ilmonen et al (2007) found that wild-derived mice that were MHC heterozygotes did not show better resistance to Salmonella or better survival in semi-natural enclosures, even though earlier laboratory experiments documented a heterozygote advantage (Penn et al 2002). These results emphasise the importance of studies on wild, outbred species.…”
Section: Effects Of the Mhc On Infection And Survival Ratesmentioning
confidence: 75%
“…Such findings may explain choice for particular MHC genotypes, although as yet there is no choice documented for genotypes identified as conferring disease resistance. In addition, while disassortative mate choice has been commonly reported, the hypothesised advantage of MHC diversity for disease resistance has received mixed empirical support, although it may be more apparent in the context of multiple infections [88,89]. Finally, particular host/pathogen interactions may not translate into MHCassociated fitness effects over a host's lifetime.…”
Section: Technical Challenges and Outstanding Questions Overcoming Tementioning
confidence: 99%
“…In some cases, there is evidence that heterozygotes actually have reduced fitness relative to homozygotes ( Wedekind et al 2005;Ilmonen et al 2007). However, a potential criticism of laboratory tests of MHC and parasite associations is that some relationships may be contextdependent and therefore only emerge under particular environmental conditions, which are hard to reproduce artificially (Bernatchez & Landry 2003;Sommer 2005;.…”
Section: Introductionmentioning
confidence: 99%